Phenomenon of Saint Vladimir in the Aspect of the Christ-Centered Worldview of V.S. Solovyov - PROSKURIAKOV, Maksim (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The purpose of the study: analysis of the phenomenon of Saint Vladimir in the aspect of the Christ-centered worldview of V.S. Solovyov. It has been determined the need to solve the following problems: to give the concept of Christ-centeredness as a fundamental characteristic of Russian Orthodoxy; to analyze the phenomenon of Saint Vladimir in the aspect of the Christ-centered worldview of Solovyov. The basics of the Christ-centered universe became the basis for creating transcendental understanding of the Truth by all Russian civil society, the foundation of the state, and legislative philosophy of understanding the russian society. RESUMEN El propósito del estudio: análisis del fenómeno de San Vladimir en el aspecto de la cosmovisión centrada en Cristo de V.S. Solovyov. Ha determinado la necesidad de resolver los siguientes problemas: dar el concepto de centrarse en Cristo como una característica fundamental de la ortodoxia rusa; analizar el fenómeno de San Vladimir en el aspecto de la cosmovisión centrada en Cristo de Solovyov. Los fundamentos del universo centrado en Cristo se convirtieron en la base para crear una comprensión trascendental de la verdad por parte de toda la sociedad civil rusa, el fundamento del estado y la filosofía legislativa para comprender la condición en la sociedad rusa.